ASPECTS OF DISCRIMINATION ON A CHARACTER WITH AIDS :A Textual Analysis on Ron Nyswaner's "Philadelphia" FUm Script - Partini, - (2008)
This study aimed to reveal how discrimination towards a character with AIDS was depicted in the screenplay of "Philadelphia" which was written by Ron Nyswaner. To conduct the study, the writer used a descriptive-qualitative design and applied close reading strategy to read the text. The data were in the form of textual evidence and obtained through reading the text. Michel Foucault's concept of power and other relevant sources were used to analyze the data. From the findings and discussion, it was revealed that discrimination towards a character with AIDS was exercised in different forms and a variety of contexts. Scared of contracting HIV/AIDS, most of the characters discriminated the infected character* Some GharaGters discriminated the infected character on behalf of institution's interest and some others exercised it on behalf of personal reasons. Therefore, discriminatory practices in the text had something to do with the issue of power. In short, discrimination was in the form of verbal (overt/covert statements) and nonverbal (unwelcome gestures and facial expressions, and the act of indifference). As a result of discrimination, resistance came up from both the subject of discrimination and others who might have sympathy for the character and concern with the issue ofHTV7AIDS.